Efficacy of antiparasitic drugs in control of gastrointestinal helminthiasis in naturally colored and white lambs from southern Brazil - Costa, Pablo Tavares; Costa, Rômulo Tavares; Kröning, Alexsandro Bahr; Fernandes, Tiago Albandes; Vaz, Ricardo Zambarda; Motta, Sara Patron da; Mendonça, Gilson de; Farias, Pâmela Peres (Medicina Veterinária, 2020)
Parasitic infections and the efficiency of different drugs were evaluated considering efficacy percentages, reduction in count of eggs per gram of feces (EPG) and larval culture in 60, 30 white and 30 naturally colored Corriedale lambs. Each phenotypic group was subdivided into six groups of five animals, each of which was administered one of the active ingredients: albendazole, levamisole hydrochloride, dysophenol, nitroxynil and moxidectin, in addition to a control group, unmedicated. Helminths were considered susceptible to nitroxinil and resistant to albendazole, levamisole, moxidectin (moderately effective) and to dysophenol (insufficiently active). In the culture of larvae, levamisole, nitroxinil and moxidectin were totally efficient (100%) against Oesophagostomum spp., moxidectin was totally efficient against Trichostrongylus spp. and nitroxinil was efficient (97%) against Haemonchus spp. Evaluating the EPG means of the phenotypic groups, it was observed higher parasitic infections in white ewes (p<0.05), in pre- and post-treatment. Therefore, it was concluded that the drug nitroxinil was the only effective for the reduction of the total parasite load of both phenotypic groups, being indicated for use in the herd in question. The genus Haemonchus spp. was the most prevalent and resistant to the drug action. Naturally colored Corriedale lambs, from the herd, showed increased resistance to gastrointestinal nematode infections.